Patient-related risk factors for predicting severity of COVID-19 infection admitted to a tertiary care hospital in Telangana - Dhanunjaya Dasari; Venkata Rambabu Mallela; K Varsha Reddy; Krishna Chaitanya Alam (Wolters Kluwer Medknow Publications, 2022)
Background: Study of factors/predictors leading to the disease severity is important. They help us for the early identification of the patients who are susceptible to develop severe form of disease. Cases with a set of unfavorable factors can be given priority attention for the management thereby it may be possible to reduce the mortality rates. Objective: The objective of this study was to study the patient-related risk factors for predicting severity of coronavirus disease 2019 (COVID-19) infection admitted to a tertiary care hospital. Methods: A hospital-based retrospective study was carried out among 305 cases of COVID-19. Hospital records of these cases were studied. Sociodemographic variables and presence of comorbidities were noted. Disease severity was classified as per the standard guidelines. It was classified as mild, moderate, and severe. Univariate and multivariate analysis was carried out. Results: Majority, i.e., 42.3% had severe disease. On univariate analysis, advanced age, coming from rural area, preexisting hypertension, being obese were significant risk factors for severe disease (P < 0.05). Those with severe disease had total risk factors score of 3.36 ± 1.68 compared to 2.48 ± 1.67 for mild or moderate disease, and this difference was statistically significant (P < 0.05). In the final model, coming from rural area and advanced age were the significant predictors of severe disease in the present study (P < 0.05). Conclusion: Advanced age and being from rural area were the significant predictors of severe disease in the present study.